Building performance analysis - Wilde, Pieter de ([Place of publication not identified] : Wiley, 2018)
Explores and brings together the existent body of knowledge on building performance analysis Building performance is an important yet surprisingly complex concept. This book presents a comprehensive and systematic overview of the subject. It provides a working definition of building performance, and an in-depth discussion of the role building performance plays throughout the building life cycle. The book also explores the perspectives of various stakeholders, the functions of buildings, performance requirements, performance quantification (both predicted and measured), criteria for success, and the challenges of using performance analysis in practice. Building Performance Analysis starts by introducing the subject of building performance: its key terms, definitions, history, and challenges. It then develops a theoretical foundation for the subject, explores the complexity of performance assessment, and the way that performance analysis impacts on actual buildings. In doing so, it attempts to answer the following questions: What is building performance' How can building performance be measured and analyzed' How does the analysis of building performance guide the improvement of buildings' And what can the building domain learn from the way performance is handled in other disciplines' -Assembles the current body of knowledge on building performance analysis in one unique resource -Offers deep insights into the complexity of using building performance analysis throughout the entire building life cycle, including design, operation and management -Contributes an emergent theory of building performance and its analysis Building Performance Analysis will appeal to the building science community, both from industry and academia. It specifically targets advanced students in architectural engineering, building services design, building performance simulation and similar fields who hold an interest in ensuring that buildings meet the needs of their stakeholders.
Foundation. Building Performance in Context -- Needs, Functions and Requirements -- Assessment. Fundamentals of Building Performance -- Performance Criteria -- Performance Quantification -- Working with Building Performance -- Impact. Design and Construction for Performance -- Building Operation, Control and Management -- High Performance Buildings -- Epilogue. Emergent Theory of Building Performance Analysis -- Appendix A: Overview of Building Performance Aspects -- Appendix B: Criterion Development Template -- Appendix C: Tool/Instrument Configuration Checklist -- Appendix D: Measurement Instruments -- Glossary -- Building Performance Abbreviations -- Generic Abbreviations -- List of Figures and Tables -- Symbols and Units.
Includes bibliographical references and index.
Title from title details screen.
Keywords: Buildings -- Performance; TECHNOLOGY & ENGINEERING / Construction / General; Buildings -- Performance; Electronic books